Rare case of human tail with tethered cord. Issue 7 (29th March 2021) - Erdogdu, Emre
Abstract: Dorsal cutaneous appendage or human tail is a rare lesion with a variable prognosis depending on the presence of associated anomalies. In the absence of structural, chromosomal abnormalities and genetic syndromes, this cutaneous lesion may be a marker for underlying occult spinal dysraphism. The evaluation of the conus medullaris can help to detect of small a skin lesions related with low‐lying spinal cord conus. We report a case of the tail with tethered cord diagnosed with ultrasound at 21 weeks of gestation.